Vstavitev dihalne cevke z uporabo airtraq laringoskopa pri bolnicah z zmerno oteženo vzpostavitvijo dihalne poti - Gerjevič, Božislava (Acta medico-biotechnica, 2011)
Purpose: The Airtraq is a single-use optical laryngoscope designed to facilitate tracheal intubation of normal and difficult airway patients. The purpose of this study was to evaluate the performance of the Airtraq in patients who possessed characteristics associated with an increased risk for difficult intubation. These characteristics were defined based on the following assessments: (1) Mallampati score, (2) thyromental distance, (3) sternomental distance, (4) Cormack and Lehane score. Methods: The present study included 29 patients with an ASA grade 1-2 who were scheduled to undergo gynaecological operations. In each patient, a direct laryngoscopy utilizing the Macintosh laryngoscope was performed prior to intubation with the Airtraq laryngoscope, and several characteristics were evaluated including visibility of the glottis, haemodynamic response, oxygenation, and intubation time. Results: The findings of this study revealed that the Airtraqsignificantly improved the view of the glottis, as compared with the Macintosh laryngoscope (p=0.02). Likewise, the mean arterial pressure significantly increased (p<0.05) during intubation, whereas the heart rate andSpO2 remained unchanged. The mean intubation time with the Airtraq was 15 seconds, and ranged from 5 to 45 seconds. Conclusion: The results from this study demonstrate that intubation using the Airtraq laryngoscope appears to beboth rapid and safe in patients who show an increased risk for difficult intubation.
Keywords: Airtraq; difficult airway; general anaesthesia; otežena vzpostavitev dihalne poti,; splošna anestezija; tracheal intubation; vstavitev dihalne cevke